ответ: х=5; у=-5;
Объяснение:
(x²-10x)+(10y+y²)+50=0
x²-10x+10y+y²+50=0
x²-10x+y²+10y+50=0
x²-10x+25-25+y²+10y+25-25+50=0
(х-5)²-25+(у+5)²-25+50=0
(х-5)²+(у+5)²=0
Сумма квадратов двух выражений равна нулю тогда и только тогда когда каждое из них равно нулю.
х-5=0, х=5;
у+5=0, у=-5
Смотри
ответ: х=5; у=-5;
Объяснение:
(x²-10x)+(10y+y²)+50=0
x²-10x+10y+y²+50=0
x²-10x+y²+10y+50=0
x²-10x+25-25+y²+10y+25-25+50=0
(х-5)²-25+(у+5)²-25+50=0
(х-5)²+(у+5)²=0
Сумма квадратов двух выражений равна нулю тогда и только тогда когда каждое из них равно нулю.
х-5=0, х=5;
у+5=0, у=-5
ответ: х=5; у=-5;
Смотри